Vowel Quality and Direction of Stress Shift in a Predictive Model Explaining the Varying Impact of Misplaced Word Stress: Evidence From English - Ghosh, Monica; Levis, John M. (Frontiers in Communication, 2021)
The use of suprasegmental cues to word stress occurs in many languages. Nevertheless, L1 English listeners’ pay little attention to suprasegmental word stress cues and evidence shows that segmental cues are more important to L1 English listeners in how words are identified in speech (Cutler, 2015; Levis, 2018; Zhang & Francis, 2010). L1 English listeners assume strong syllables with full vowels mark the beginning of a new word, attempting alternative resegmentations only when this heuristic fails to identify a viable word string (Cutler & Butterfield, 1992; Cutler & Carter, 1987). English word stress errors have been shown to severely disrupt processing for both L1 and L2 listeners (Benrabah, 1997; Cutler, Dahan & van Donselaar, 1997; Field, 2005), but not all word stress errors are equally damaging (Cutler, 1986; Slowiaczek, 1990). Vowel quality (Bond & Small, 1983; Cutler, 2015) and direction of stress shift (Cutler & Clifton, 1984; Field, 2005) are thought to be predictors of the intelligibility of nonstandard stress pronunciations—but most research so far on this topic has been limited to two-syllable words (e.g., Yu & Andruski, 2010). The current study uses auditory lexical decision and delayed word identification tasks to test a hypothesized English Word Stress Error Gravity Hierarchy for words of two to five syllables. Results indicate that English word stress errors affect intelligibility most when they introduce concomitant vowel errors, an effect that is somewhat mediated by the direction of stress shift. As a consequence, the relative intelligibility impact of any particular lexical stress error can be predicted by the Hierarchy for both L1 and L2 English listeners. These findings have implications for L1 and L2 English pronunciation research and teaching. For research, our results demonstrate that varied findings about loss of intelligibility are connected to vowel quality changes of word stress errors and that these factors must be accounted for in intelligibility research. For teaching, the results indicate that not all word stress errors are equally important, and that only word stress errors that affect vowel quality should be prioritized.